Disconnection Syndrome and Verbal, Spatial and Tactile Amnesia following a Tumor of the Splenium of the Corpus Callosum - Marina Scarpa; Paolo Sorgato (Behavioural Neurology)
A patient with a severe amnesic syndrome following a glioma of the splenium of the corpus callosum is reported. The long-term memory deficit involved anterograde as well as retrograde events dating back to 40 years and causing topographical disorientation. Short-term memory test performance was in the normal range, with the exception of tactile memory which was severely impaired. The patient also showed disconnection symptoms, due to severing of occipito-parietal and parieto-temporal connections, while parieto-parietal connections were undamaged.